High power supercap electrodes based on vertical aligned carbon nanotubes on aluminum - Doerfler, S.; Felhoesi, I.; Marek, Tamás; Thieme, S.; Althues, H.; Nyikos, Lajos; Kaskel, Stefan (Journal of Power Sources, 2013)
A scalable process at atmospheric pressure for direct growth of vertical aligned carbon nanotube (VA-CNT) on aluminum substrates has been developed including dip-coating steps for the wet-chemical buffer and catalyst layer deposition and a subsequent chemical vapor deposition step. Up to 80 μm high vertical aligned carbon nanotube forests were obtained on catalyst-coated aluminum foil in a thermal plasma-free CVD process at atmospheric pressure and 645 °C using ethene as carbon source. The influence of two catalyst compositions (Fe:Co 2:3 and Fe:Mo 47:3) and the effect of the catalyst concentration on growth rate, morphology and density of resulting CNT films were investigated. Additionally, the binder-free VA-CNT/aluminum system was electrochemically tested as supercap electrode and the feasibility of tailoring the specific capacity varying the catalyst layer thicknesses was shown. The specific capacitance of electrodes deduced from impedance spectra varied between 25.6 and 61.2 F g-1 depending on the catalyst complex mixture composition and concentration. The VA-CNT/Al electrodes have a very low value of effective serial resistance (0.42-0.15 mΩ g) indicating a potential candidate as electrode material for high power supercapacitor application. Excellent cycle stability of supercapacitors has been demonstrated up to 300,000 cycles. © 2012 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Aluminum; Atmospheric pressure CVD; High power; Supercapacitor; Vertical aligned carbon nanotube